2016
DOI: 10.12738/estp.2016.6.0227
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Academic Achievement of Middle Schoolers in Turkey

Abstract: The purpose of this study is to discuss student and school factors, including cross level interaction, that cause inequalities in seven and eighth grade students' achievement in Turkish context by using national achievement test scores with a multi-level statistical approach. Our results are in line with most other studies with similar purpose. Our results show that approximately 17% of the variation in student test scores is explained by differences between schools, while the remainder of the variation is acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
(50 reference statements)
1
2
1
2
Order By: Relevance
“…Female students had higher average GPA scores than male students after controlling other variables. This finding is consistent with several studies (Börkan & Bakış, 2016;Dayioğlu & Türüt-Aşık, 2007;Engin-Demir, 2009;Ferreira & Gignoux, 2010;Gevrek & Seiberlich, 2014;Güvendir, 2014;Van Houtte, 2004). For example, Engin-Demir ( 2009) studied with sixth, seventh, and eighth grade students to investigate factors influencing their academic success by using their GPA.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Female students had higher average GPA scores than male students after controlling other variables. This finding is consistent with several studies (Börkan & Bakış, 2016;Dayioğlu & Türüt-Aşık, 2007;Engin-Demir, 2009;Ferreira & Gignoux, 2010;Gevrek & Seiberlich, 2014;Güvendir, 2014;Van Houtte, 2004). For example, Engin-Demir ( 2009) studied with sixth, seventh, and eighth grade students to investigate factors influencing their academic success by using their GPA.…”
Section: Discussionsupporting
confidence: 86%
“…Diğer değişkenler kontrol edildiğinde, kız öğrenciler erkek öğrencilere göre daha yüksek başarı ortalamasına sahiptir. Bu araştırma sonucu diğer araştırma sonuçları ile benzerlik göstermektedir (Börkan & Bakış, 2016;Güvendir, 2014;Engin-Demir, 2009;Van Houtte, 2004). Araştırmalar bazı sebeplerden dolayı kız öğrencilerin erkek öğrencilere göre daha iyi performans gösterdiklerini ortaya koymaktadır.…”
Section: Journal Of Measurement and Evaluation In Education Andunclassified
See 2 more Smart Citations
“…As can be seen in Figure , SES is the third and the second significant variable that predicted science achievement in LAS and HAS, respectively. Although these findings may seem to contradict the results of the previous studies that reported the predominant effect of SES on other variables in science achievement (Alacacı & Erbaş, ; Börkan & Bakış, ; Kalender & Berberoglu, ), they confirm results from other studies which indicate that students cluster in schools according to their SES in Turkey (Alacacı & Erbaş, ; Dincer & Uysal, ). In other words, in this study, because schools were classified based on their science achievement, this methodological design might act as a confounder for the effect of SES on achievement.…”
Section: Discussioncontrasting
confidence: 69%